Socio-Demographic Profile, Knowledge and Awareness Level of Teenage Mothers (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Teenage pregnancy is coming up as one of the most important social and public health problem in both developed and developing countries. Lack of knowledge and poor awareness lead to increase number of teenage pregnancy. To assess the knowledge and awareness level of teenage mothers and its consequences. Materials and methods: A cross-sectional observational study was conducted at the Obstetrics and Gynaecology Department of Chittagong Medical College Hospital, Chittagong for a period of six months from 10th October 2013 to 9th April 2014. One hundred teenage mothers (Aged 15-19 completed years at delivery) who got herself admitted to the department of Obstetrics and Gynaecology were included in this study. Predesigned data collections sheet was used and relevant informations were recorded. Results: Among 100 patients, 60 % mothers were in age group of 17-18 years. 25% 19 years, 15% in